A Nonsecosteroidal Vitamin D Receptor Modulator Ameliorates Experimental Autoimmune Encephalomyelitis without Causing Hypercalcemia. (23rd December 2010) - Na, Songqing; Ma, Yanfei; Zhao, Jingyong; Schmidt, Clint; Zeng, Qing Q.; Chandrasekhar, Srinivasan; Chin, William W.; Nagpal, Sunil
Abstract : Vitamin D receptor (VDR) agonists are currently the agents of choice for the treatment of psoriasis, a skin inflammatory indication that is believed to involve an autoimmune component. 1, 25-dihydroxyvitamin D3 [1, 25-(OH)2 D3 ], the biologically active metabolite of vitamin D, has shown efficacy in animal autoimmune disease models of multiple sclerosis, rheumatoid arthritis, inflammatory bowel disease, and type I diabetes. However, the side effect of 1, 25-(OH)2 D3 and its synthetic secosteroidal analogs is hypercalcemia, which is a major impediment in their clinical development for autoimmune diseases. Hypercalcemia develops as a result of the action of VDR agonists on the intestine. Here, we describe the identification of a VDR modulator (VDRM) compound A that was transcriptionally less active in intestinal cells and as a result exhibited less calcemic activity in vivo than 1, 25-(OH)2 D3 . Cytokine analysis indicated that the VDRM not only modulated the T-helper cell balance from Th1 to Th2 effector function but also inhibited Th17 differentiation. Finally, we demonstrate that the oral administration of compound A inhibited the induction and progress of experimental autoimmune encephalomyelitis in mice without causing hypercalcemia.